Immunogenetics in sickle cell disease - Maio, Karina Tozatto (2019)
Sickle cell disease (SCD) is the most common inherited hemoglobinopathy, caused by a single nucleotide polymorphism (SNP) in the beta-globin (HBB) gene. This SNP determines the synthesis of S haemoglobin (HbS), which polymerizes under stress conditions, sickling the red blood cell (RBC). Sickle RBC are less deformable, more adherent to the endothelium, and more susceptible to haemolysis. SCD complications are explained by the interaction between haemolysis, vaso-occlusion and inflammatory activation, determined by the RBC sickling. Patients with SCD may present several complications, affecting all organs. Clinical presentation is very heterogeneous, ranging from patients who have mild symptoms to patients who die from disease complications. Because inflammation plays a major role in SCD, polymorphisms in inflammatory genes are potential targets to explain this heterogeneity. Haematopoietic stem cell transplantation (HSCT) is the only curative therapy currently available for SCD, with good results shown after human leukocyte antigen (HLA) identical sibling HSCT. However, most patients will not have a matched sibling donor. Patients with SCD are mostly from African origin, the less represented ethnic group in stem cell donor registries. To date, few studies using local registries were performed to find the probability of having a potential unrelated donor in SCD settings. This study aimed to assess the role of inflammatory genes encoding Toll-like receptors (TLR) in the occurrence of bacterial infections in patients with SCD, because infection is a leading cause of mortality in SCD, and TLR recognize a wide range of bacteria. Patients included had DNA samples and clinical data available. SNPs were genotyped by real-time polymerase chain reaction (RT-PCR). Four hundred thirty patients, mostly from Brazilian and Sub-Saharan African origin, were divided in two groups: infected (n=235, patients who presented at least one episode of bacterial infection), and non-infected (n=195, patients who never presented bacterial infections). The T/A genotype of SNP rs4696480 in TLR2 was less frequent in infected patients (50% versus 67%, OR=0.50, 95% CI 0.34-0.75, p<0.001). In addition, the T/T genotype of this SNP was more frequent among infected patients (15% versus 5%, OR=0.50, 95% CI 0.34-0.75, p<0.001). Previous reports in other settings showed that A/A carriers had higher secretion of inflammatory markers, while T allele was associated with less occurrence and severity of inflammatory diseases. Hence, T/A genotype might express the ideal inflammatory response to defeat bacteria, while the weaker inflammatory response determined by the T/T genotype increases susceptibility to bacterial infections in SCD settings. Our study also aimed to estimate the probability of finding a potential human leukocyte antigen (HLA) allele matched (loci HLA-A, HLA-B and HLA-DRB1) unrelated donor for patients with SCD in international donor searches. In this study, 185 patients were included, 116 from a Brazilian centre, and 69 who underwent related or unrelated HSCT from an HLA identical or non-identical donor in transplant centres reporting to the European Society for Blood and Marrow Transplantation (EBMT). Patients had HLA data available in intermediate or high resolution. HLA haplotypes were estimated using HaploStats software and classified according to ethnicity. Next, we performed donor searches in international stem cell donor registries (WMDA). Although most haplotypes were African, Brazilian patients had more haplotypes from other ethnic groups. However, Brazilian patients and EBMT patients had the same chances of having at least one potential allelic 6/6 donor in donor registries, of 47% and 47% respectively. Most donors were from the National Marrow Donor Program (NMDP) registry (USA) and from the Brazilian donor registry (REDOME). We reported a higher probability of finding a matched unrelated donor than previous studies using local registries, however strategies are needed to ameliorate representativity of ethnic groups in donor registries. Altogether, our findings on genetic modulation of SCD might contribute to predict potentially severe complications in patients with SCD. Identifying patients at high risk for some complications will help to ameliorate guidelines for diagnosis and management. In addition, given the importance of early referral to HSCT in SCD, predicting the chances of having a potential donor will also influence therapy decisions. Furthermore, our results support the necessity of improving alternative donor sources and new therapies for SCD.